Legalitas Penerbitan SHGB dan SHM di Wilayah Laut (Studi pada Kasus Pagar Laut di Kawasan Reklamasi Pantai Indah Kapuk) - Widyarsih, Rahajeng; Sujono, Sujono; Sudarto, Sudarto (LITERATUS, 2025)
This article discussesnganalyze the legal violations that occurred in the case of the construction of a sea fence as part of the Pantai Indah Kapuk (PIK) reclamation project in Tangerang as well as the Issuance of Building Use Rights (HGB) and Ownership Certificates (SHM) in the sea area which is a complex and controversial issue in Indonesia. The purpose of this study is to determine the legality of the issuance of HGB and SHM in the sea area reviewed from the Basic Agrarian Law (UUPA) and other related laws and regulations and to analyze how the Sea Fence case is resolved. The methodology used in this analysis includes a literature review of various related laws and regulations, a study of project planning documentation, and interviews with environmental and spatial law experts. The analytical approach used focuses on the normative legal aspects by considering the empirical facts that occur in the field. This study also considers the jurisprudence of similar cases that have occurred previously in Indonesia. The results of this study found that it was concluded that the legality of issuing HGB and SHM in the sea area is a complex issue and contradicts the provisions of Article 27 of Law Number 1 of 2014 concerning Management of Coastal Areas and Small Islands. (Law No. 1/2014). The issuance of land rights in the sea area must be carried out very carefully and considering all legal implications as regulated in Presidential Regulation Number 122 of 2012 concerning Reclamation in Coastal Areas and Small Islands. (Presidential Regulation No. 122/2012). This study also revealed complex and multidimensional legal violations in the case of the Pantai Indah Kapuk Tangerang Reclamation Project sea fence. The developer of the PIK 2 area needs to carry out criminal and civil liability based on Law No. 32/2009 and the Criminal Code, through the settlement of applicable laws.